Impacts of Tropical Cyclones on Longleaf Pine Ecosystems of Florida: Tropical Cyclogenesis, Landfall Frequencies, and Climate Change - Gilliam, Frank S. (Frontiers in Ecology and Evolution, 2021)
Tropical storms and hurricanes (collectively hereafter, tropical cyclones) are among the most destructive forces in nature, with a total energy yield far exceeding that of volcanic eruptions and seismic activity. In addition to damaging winds, land-fall tropical cyclones generate excessive rain and storm surge, which commonly combine to create serious flooding. These threats are of particular concern to coastal areas of the southeastern United States, most especially in the State of Florida. This paper reviews environmental factors that lead to tropical cyclone formation, with a specific focus on (1) storm history and spatial distribution in Florida, and (2) the potential relationship between climate change and the frequency of tropical cyclones in the North Atlantic Ocean. Tropical cyclones are formed from a complex combination of meteorological conditions, driven primarily by the release of excess heat from the surface waters of the ocean, along with an unstable atmosphere comprising air temperatures decreasing and wind speeds increasing with altitude. Among the coastal counties (or parishes and boroughs, where appropriate) from Texas to Maine, Florida has experienced by far the highest frequency of tropical cyclones, especially the southern tip of peninsular Florida, with its most populous county (Miami-Dade) receiving 25 hits from 1900 to 2010, second only to Monroe County (32 hits) during that period. Frequencies of all categories of cyclones (tropical storms, hurricanes, major hurricanes) have exhibited statistically-significant increases from 1850 to the present. Cyclone frequencies were significantly correlated with increases in mean air and ocean temperatures, both of which have increased over the past, suggesting a causal relationship with anthropogenic climate change.